Proprietary rights and insolvency - Calnan, Richard (Oxford : Oxford University Press, 2010)
'This topical title explains the circumstances in which a creditor of an insolvent debtor can take priority over other creditors by claiming a proprietary interest in assets held by the debtor. It focuses on the situation where the proprietary interests are created by operation of law or implied from the arrangements between the parties, rather than by express transfer or taking of security. The book clarifies the current state of the law in an important area of insolvency law (especially in times of economic crisis) where the law is not settled, taking into account the latest developments in case law, and suggesting how it might be simplified by going back to first principles, such as the way proprietary interests are transferred at common law and in equity. The book concerns both insolvency law and property law, being essentially concerned with the limits of the law of property, marking out its boundary with the law of obligations. It is of particular importance in common law systems because of the nature of equitable proprietary interests, and includes reference to Commonwealth authorities where relevant, including Australia, New Zealand and Canada. This work provides a structured and principled analysis of the topical and important area of creditors' proprietary rights in the event of insolvency of a debtor'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Priorities of claims and liens -- England